Implementation of Educational Games Using the Levenshtein Distance Algorithm for Improving Elementary School Students' Word Vocabulary Android - Rio Dwi Cahya; Nenna Irsa Syahputri (Journal of Technology and Computer, 2026)
The low motivation of elementary school students in learning Indonesian vocabulary through conventional methods is needed, so an innovative technology-based approach is needed that is able to combine elements of learning and entertainment. Scramble educational games are designed with a mechanism of randomizing letters from a word that must be rearranged by students into correct words. In the answer validation process, the Levenshtein Distance algorithm is used to measure the error rate based on the minimum number of edit operations (substitution, insertion, or deletion) required for the guessed word to be equal to the target word. With the application of this algorithm, the system is not only able to provide a binary right or wrong assessment, but also assess the degree of closeness of students' answers to the supposed word. This allows for more adaptive and educational feedback, such as "almost correct" when the editing distance is low, thus encouraging students to improve answers with more confidence. This research also emphasizes the ease of use through the Android platform, given the high penetration of mobile devices among the public, including elementary school students. The results of the implementation show that the Levenshtein Distance algorithm-based scramble educational game is effective in increasing learning motivation and enriching students' vocabulary, while providing an alternative interactive learning method that is relevant to the development of educational technology.